A novel urine analysis technique combining affinity chromatography with Au nanoparticle based surface enhanced Raman spectroscopy for potential applications in non‐invasive cancer screening. Issue 4 (26th December 2018) - Lin, Xueliang; Wang, Lingna; Lin, Huijing; Lin, Duo; Lin, Jinyong; Liu, Xiujie; Qiu, Sufang; Xu, Yuanji; Chen, Guannan; Feng, Shangyuan
Abstract : Modified nucleoside in urine samples is one of the most common biomarkers for cancer screening. Therefore, we developed a novel detection method for modified nucleoside detection in human urine. In this work, the modified nucleoside from real cancer patient's urine samples was first separated and purified using the affinity chromatography (AC) technology relying on its specific adsorption capacity. Then, surface‐enhanced Raman spectroscopy (SERS) technology with the capability of single molecular detection was used to sensitively characterize the biomolecular features of modified nucleoside. A total of 141 high‐quality SERS spectra of urinary modified nucleoside can be obtained from 50 gastric cancer patients and 43 breast cancer patients, as well as 48 healthy volunteers. Using principal component analysis combined with linear discriminant analysis (PCA‐LDA), the diagnostic sensitivities for identifying gastric cancer vs normal, breast cancer vs normal, gastric cancer vs breast cancer were 84.0%, 76.7% and 82.0%, respectively, and the corresponding diagnostic specificities for each combination were 95.8%, 87.5% and 90.7%, respectively. These results show that this novel method based on urinary modified nucleoside detection combining AC and SERS technologies holds promising potential for developing a specific, non‐invasive and label‐free tool for cancer screening. Abstract : The combination of surface‐enhanced Raman spectroscopy technology and affinity chromatography was used as a rapid and label‐free method to identify gastric cancer, breast cancer and healthy human urine samples.